Natural Selection and Contrastive Explanation. Issue 3 (July 2019) - Witteveen, Joeri
Abstract : This article defends the Negative View of natural selection explanation, according to which natural selection cannot explain of any given individual why it has the traits it does. Over the years, this view has been criticized on empirical, metaphysical, and explanatory grounds. I review the debate and offer additional reasons for rejecting the empirical and metaphysical objections. The explanatory objection, which holds that the Negative View is rooted in a flawed account of contrastive explanation, initially seems plausible. However, I argue that a closer consideration of the desiderata of contrastive explanation shows that this objection fails as well.